Characteristics of intracellular algogenic organic matter and its reactivity with hydroxyl radicals. (1st November 2018) - Lee, Doorae; Kwon, Minhwan; Ahn, Yongtae; Jung, Youmi; Nam, Seong-Nam; Choi, Il-hwan; Kang, Joon-Wun
Abstract: The aim of this study was to investigate the reactivity of intracellular algogenic organic matter (IOM) with hydroxyl radicals (·OH), a key reaction species in advanced oxidation processes. IOM was extracted from two green algae, Chlamydomonas reinhardtii and Scenedesmus sp., and two blue-green algae, Anabaena sp. and Microcystis aeruginosa using a freeze–thaw method. The second-order rate constants of the extracted IOM with ·OH were determined as 7.95 × 10 8 MC −1 s −1 ( Chlamydomonas reinhardtii ), 6.71 × 10 8 MC −1 s −1 ( Scenedesmus sp.), 4.02 × 10 8 MC −1 s −1 ( Anabaena sp.), and 4.45 × 10 8 MC −1 s −1 ( Microcystis aeruginosa ). These rate constants were significantly higher than values reported for dissolved organic matter in various water sources. This implies that IOM formation during algal bloom season could change the ·OH water matrix demand and adversely affect the performance of advanced oxidation processes. To investigate the physical and chemical composition characteristics of IOM and their relationship to the rate constants determined for the reaction between IOM and ·OH, liquid chromatography-organic carbon detection (LC-OCD) and fluorescence excitation-emission matrix & parallel factor analysis (FEEM-PARAFAC) were used. The IOM mainly consisted of low molecular weight (LMW) matter and protein-related compounds, as evidenced LMW neutrals (38–65%), biopolymers (7–19%), and tryptophan-like compounds (74–94%). Based on the composition characteristics of IOM, it was concluded that the molecular weight and the presence of nitrogen-containing compounds are influential parameters for determining the reactivity of IOM with ·OH. Highlights: The ·OH reactivity of IOM was determined as 4.02–7.95 × 10 8 MC −1 s −1 . IOM had 2–6 times higher ·OH reactivity than previously reported DOM. The characteristic of IOM was investigated using LC-OCD and FEEM-PARAFAC. IOM mainly consisted of low molecular weight neutrals and tryptophan-like compounds. The algae bloom could change the reactivity of DOM with ·OH.